Research on slurry diffusion and seepage law in mining overburden fractures based on CFD numerical method - Cao Zhengzheng; Jia Yunlong; Li Zhenhua; Du Feng (Scientific Reports, 2023)
Abstract It is of great theoretical significance and engineering application value to research the diffusion law of slurry in mining fractures of rock strata to enrich grouting theory and improve grouting sealing effect. In this paper, the law of grout diffusion in fractures under different working conditions is systematically explored and analyzed, and a numerical simulation scheme of grout diffusion in a single slab crack is established. Then, the diffusion law of grouting slurry in crack under different rheological index and different consistency index is further investigated. The results show that the diffusion time of grouting slurry has no relation with the rheological index. The grout pressure at the same point increases with the increase of rheological index. When the rheological index increases by 0.1, the grout pressure increases by about 12.5%. The closer the grouting mouth is, the more the grouting pressure is affected by the rheological index. There is little relationship between the diffusion time of grouting slurry and consistency index. The grout pressure at each measurement point increases with the increase of the consistency index. When the consistency index increases by 1, the grout pressure increases by about 15% on the basis of the origin. The closer the grouting mouth is, the more the grouting pressure is affected by the consistency index. In engineering practice, when grouting slurry with large rheological index or consistency index exists, it is necessary to moderately increase the grouting pressure value.